The relationship between smartphone addiction and sleep disorder among college students: negative emotions as a mediator and gender as a moderator - Li, Siyi; Deng, Yingying; Cai, Lihong; Wu, Linlin (Frontiers in Psychiatry, 2025)
BackgroundCollege students are disproportionately affected by smartphone addiction, which has been linked to various health impairments, including sleep disorders. This study explores the relationship between smartphone addiction and sleep disorders, with a focus on negative emotions as a mediator and gender as a moderator.MethodsCluster sampling was used to survey 1056 Chinese college students. The Mobile Phone Addiction Index, Negative Affect Scale, and Sleep Disorder Scale were administered. Versions of SPSS 27.0 and PROCESS macro 4.0 were used for data analysis, employing Models 15 and 4 to examine moderation and mediation, respectively.ResultsA strong direct correlation was identified between smartphone addiction and sleep disorder, with negative emotions mediating this relationship, accounting for 33.7% of the effect. Gender significantly moderated the mediation process, with females demonstrating a greater correlation than males between sleep disorders and negative emotions.ConclusionNegative emotions partially mediated smartphone addiction’s association with sleep disorder, whereas gender significantly moderated this mediation. These findings underscore the complex dynamics among smartphone addiction, emotional well-being, and sleep among college students.